Lactobacillus rhamnosus GG ameliorates noise-induced cognitive deficits and systemic inflammation in rats by modulating the gut-brain axis - Li, Xiaofang; Zheng, Pengfang; Cao, Wa; Cao, Yang; She, Xiaojun; Yang, Honglian; Ma, Kefeng; Wu, Fangshan; Gao, Xiujie; Fu, Yu; Yin, Jiayi; Wei, Fei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Environmental noise exposure is linked to neuroinflammation and imbalance of the gut microbiota. Promoting gut microbiota homeostasis may be a key factor in relieving the deleterious non-auditory effects of noise. This study aimed to investigate the effect of Lactobacillus rhamnosus GG (LGG) intervention on noise-induced cognitive deficits and systemic inflammation in rats. Methods: Learning and memory were measured using the Morris water maze, while 16S rRNA sequencing and gas chromatography-mass spectrometry were used to analyze the gut microbiota and short-chain fatty acid (SCFA) content. Endothelial tight junction proteins and serum inflammatory mediators were assessed to explore the underlying pathological mechanisms. Results: The results indicated that Lactobacillus rhamnosus GG intervention ameliorated noise-induced memory deterioration, promoted the proliferation of beneficial bacteria, inhibited harmful bacteria, improved dysregulation of SCFA-producing bacteria, and regulated SCFA levels. Mechanistically, noise exposure led to a decrease in tight junction proteins in the gut and hippocampus and an increase in serum inflammatory mediators, which were significantly alleviated by Lactobacillus rhamnosus GG intervention. Conclusions: Taken together, Lactobacillus rhamnosus GG intervention reduced gut bacterial translocation, restored gut and blood-brain barrier functions, and improved gut bacterial balance in rats exposed to chronic noise, thereby protecting against cognitive deficits and systemic inflammation by modulating the gut-brain axis.